Reconstructing larval growth and habitat use in an amphidromous goby using otolith increments and microchemistry. Issue 4 (19th December 2016) - Hogan, J. D.; Kozdon, R.; Blum, M. J.; Gilliam, J. F.; Valley, J. W.; McIntyre, P. B.
Abstract : High‐resolution analysis of growth increments, trace element chemistry and oxygen isotope ratios ( δ 18 O) in otoliths were combined to assess larval and post‐larval habitat use and growth of Awaous stamineus, an amphidromous goby native to Hawai'i. Otolith increment widths indicate that all individuals experience a brief period of rapid growth during early life as larvae and that the duration of this growth anomaly is negatively correlated with larval duration. A protracted high‐growth period early in larval life is associated with a lower ratio of Sr:Ca, which may reflect low salinity conditions in nearshore habitats. A distinct shift in δ 18 O (range: 4–5‰) is closely associated with the metamorphic mark in otoliths, indicating that larval metamorphosis occurs promptly upon return to fresh water. Strontium and other trace elements are not as tightly coupled to the metamorphosis mark, but confirm the marine‐to‐freshwater transition. Integration of microstructural and microchemical approaches reveals that larvae vary substantially in growth rate, possibly in association with habitat differences. Although time and financial costs make it difficult to achieve large sample sizes, present results show that examining even a small number of individuals can lead to novel inferences about early life history in diadromous fishes and illustrates the value of integrating analyses.